Deep Insights in Circular RNAs: from biogenesis to therapeutics - Peerzada Tajamul Mumtaz; Qamar Taban; Mashooq Ahmad Dar; Shabir Mir; Zulfkar ul Haq; Sajad Majeed Zargar; Riaz Ahmad Shah; Syed Mudasir Ahmad (Biological Procedures Online, 2020)
Abstract Circular RNAs (circRNAs) have emerged as a universal novel class of eukaryotic non-coding RNA (ncRNA) molecules and are becoming a new research hotspot in RNA biology. They form a covalent loop without 5′ cap and 3′ tail, unlike their linear counterparts. Endogenous circRNAs in mammalian cells are abundantly conserved and discovered so far. In the biogenesis of circRNAs exonic, intronic, reverse complementary sequences or RNA-binding proteins (RBPs) play a very important role. Interestingly, the majority of them are highly conserved, stable, resistant to RNase R and show developmental-stage/tissue-specific expression. CircRNAs play multifunctional roles as microRNA (miRNA) sponges, regulators of transcription and post-transcription, parental gene expression and translation of proteins in various diseased conditions. Growing evidence shows that circRNAs play an important role in neurological disorders, atherosclerotic vascular disease, and cancer and potentially serve as diagnostic or predictive biomarkers due to its abundance in various biological samples. Here, we review the biogenesis, properties, functions, and impact of circRNAs on various diseases. Graphical Abstract